Lessons from Israel's COVID-19 Green Pass program - Shelly Kamin-Friedman; Maya Peled Raz (BMC, 2021)
Abstract As of the beginning of March 2021, Israeli law requires the presentation of a Green Pass as a precondition for entering certain businesses and public spheres. Entitlement for a Green Pass is granted to Israelis who have been vaccinated with two doses of COVID-19 vaccine, who have recovered from COVID-19, or who are participating in a clinical trial for vaccine development in Israel. The Green Pass is essential for retaining immune individuals' freedom of movement and for promoting the public interest in reopening the economic, educational, and cultural spheres of activity. Nonetheless, and as the Green Pass imposes restrictions on the movement of individuals who had not been vaccinated or who had not recovered, it is not consonant with solidarity and trust building. Implementing the Green Pass provision while advancing its effectiveness on the one hand, and safeguarding equality, proportionality, and fairness on the other hand may imbue this measure with ethical legitimacy despite involving a potential breach of trust and solidarity.